HIF1A acts as target of XiHuang Pill in the treatment of papillary thyroid cancer by regulating dedifferentiation - Yu, Xu-Zhe; Zhu, Wei-Li; Qian, Hua-Chun; Sun, Chun-Jiang (Frontiers in Chemistry, 2025)
BackgroundPapillary thyroid carcinoma (PTC) is the most common subtype of thyroid cancer and has shown a rising incidence globally. Despite its generally favorable prognosis, recurrence and therapeutic resistance remain challenges in clinical management. Traditional Chinese Medicine, particularly Xihuang Pill (XHP), has demonstrated promising anticancer potential in various tumors, but its molecular mechanisms in PTC remain unclear. This study aimed to explore the targets of XHP in the treatment of PTC.MethodsThe active ingredients of XHP were first obtained, and ingredients and PTC-related targets were identified, followed by enrichment analysis. Protein-protein interaction (PPI) network was constructed to determine the key ingredients and targets, and then molecular docking was conducted. Key targets’ prognostic role, correlation with differentiation, and immune infiltration level were analyzed based on the TCGA data. In vitro experiments were then performed to validate the role of HIF1A. Finally, the association of clinical characteristics with HIF1A was also assessed.ResultsFirstly, 132 common targets were associated with XHP and PTC, enriched in MAPK, PI3K-AKT, and HIF-1 signal pathways. Five hub genes (CCND1, ESR1, AKT, HIF-1A, BCL2) and 2 ingredients were found, with a favorable combination between them. AKT1 and HIF1A were upregulated in PTC, and high expressions of them were related to poor prognosis (all P < 0.05). Further, only HIF1A was upregulated in the advanced stage of PTC and significantly correlated with the dedifferentiation (all P < 0.05). HIF1A upregulation also correlated with the decrease of activated NK cells abundance in PTC (all P < 0.05), while NK cell abundance showed positive correlation with differentiation level (P < 0.05). HIF1A inhibited differentiation of PTC cells, while XHP suppressed PTC progression and promoted differentiation by downregulating HIF1A. Finally, histopathological type and positive lymph node number correlated with HIF1A expression (all P < 0.05).ConclusionThis study systematically elucidated the potential mechanisms by which XHP exerts anti-PTC effects, highlighting that HIF1A is a promising target of XHP in the treatment of PTC by regulating dedifferentiation. These findings provide a scientific basis for the application of XHP in PTC.